Profil poznawczo-osobowościowy ponadprzeciętnie uzdolnionych dorosłych uczniów języka obcego - Biedroń, Adrianna (Neofilolog, 2012)
The purpose of this article is to present a report of a study on cognitive and personality factors in 44 gifted foreign language learners. The cognitive factors tested were the following: foreign language aptitude, intelligence and working memory. The personality factors included the Five Factor Model of personality, locus of control and style of coping with stress, among others. The results of the study are presented and discussed with regard to contemporary research on foreign language aptitude.